Synthesis, Characterization, Magnetic and Catalytic Properties of a Ladder‐Shaped MnII Coordination Polymer. Issue 23 (15th July 2014) - Lymperopoulou, Smaragda; Papastergiou, Maria; Louloudi, Maria; Raptopoulou, Catherine P.; Psycharis, Vassilis; Milios, Constantinos J.; Plakatouras, John C.
Abstract: [Mn(LH)(H2 O)] n 1, where LH 2– is the dianion of N ‐(4‐carboxybenzyl)iminodiacetic acid has been synthesized and its crystal structure has been determined. The crystal of1 is built from 1D polymeric ladder‐shaped chains that extend to a 3D supramolecular architecture through H‐bonds. The compound was characterized with spectroscopic and physicochemical techniques. Variable‐temperature magnetic data suggest that there are weak antiferromagnetic interactions. Compound1 has been evaluated as a heterogeneous oxidation catalyst. It catalyzes alkene epoxidation selectively in relatively high yields. Abstract : A new ladder‐shaped Mn II coordination polymer (CP) with a N‐substituted iminodiacetate ligand has been synthesized and characterized. It demonstrates catalytic activity as a heterogeneous catalyst for the epoxidation of alkenes in the presence of H2 O2 .